Determination of technical condition of high-pressure pump and injectors of MAN B&W 6S50MC-C marine diesel engine by changing the pressure and temperature in pipeline - L. Yu. Volkova (Омский научный вестник)
The purpose of the work is to propose methods and means for determining the technical condition of fuel equipment. A method is proposed for determining the technical condition of the high-pressure pump and injectors of the marine diesel MAN B&W 6S50MC-C by changing the maximum fuel pressure and temperature of the outer surface of the pipeline. For fuel equipment with a maximum pressure in the pipeline from 50 to 150 MPa, the permissible pressure change zone is determined. A formula is proposed that additionally takes into account the cyclic fuel supply and its mass when estimating the temperature from its compression by the pump plunger. The fuel temperature during compression is determined depending on the pressure value. The calculation of the heat transfer process through the pipeline wall and from the heated wall surface to the air is performed. A portable RGK PL12 pyrometer is proposed to measure the temperature on the pipeline surface and determine the technical condition of the fuel equipment. The permissible temperature change zone of the pipeline surface is given, according to which the serviceable condition of the pump and the nozzle is evaluated.